EFFECT OF WOUND CARE ON WOUND HEALING PROCESS OF POST OPERATION IN PATIENTS APENDEKTOMY IN RS DUSTIRA CIMAHI - Marlin Sutrisna; Vega M Tusyanawati (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2021)
ABSTRACTVega M. Tusyanawati1, Marlin Sutrisna2, Tonika Tohri3  Sekolah Tinggi Ilmu Kesehatan Rajawali Bandung IndonesiaEmail : vegatusyanawati@gmail.comBackground: Appendicitis is one of the emergency  cases in the abdominal area with a major complaint of persistent lower abdominal pain that develops and increased pain. An appendectomy is a surgical intervention that has the purpose of ablative surgery or removal of body parts that contain problems or have disease. One of the postoperative treatments of apendectomy is with wound care. The current wound care treatment is modern and conventional wound care. Objective: This study was to investigate the effect of treatment of postoperative wound healing apendectomy. Methodology: The design used in this research is Quasi Experiment, with posttest-only design approach. The number of samples taken is 18 respondent. Taking sampling with accidental sampling technique. Result: The result shows that p-value 0.001, with mean value in intervention group was 5.50 and in control group 13.50. Conclusion: There is a significant difference in the wound healing process using conventional and modern wound care.Keywords                    : type of wound care, post operative apendectomy